Pendampingan Aplikasi Akuntansi pada Badan Usaha Milik Desa (BUMDes) Mitra Kencana - Rofiud Darajah; Azka Dwi Fachrurazi; Andrian Putra; Ahmad Fauzain Al Kayyis; Meilinda Maulidya Widiyanti; Afrijal Ramadani; Dessy Putri Andini (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
BUMDes Mitra Kencana plays a strategic role in fostering village economic development but faces challenges in financial management due to the use of manual recording systems. This community service program aims to enhance the capacity of BUMDes administrators through the implementation of a user-friendly accounting application that complies with standard practices. The method involved initial surveys, socialization, observation, and structured, ongoing technical assistance. The results indicate that BUMDes administrators were able to understand and utilize the accounting application for more efficient and accurate financial recording and reporting. Furthermore, the program facilitated the development of new business initiatives, such as clean water management. This assistance not only improved the professionalism of financial governance within BUMDes but also encouraged greater independence and transparency in decision-making.